Mineral Industries Of The Middle East - Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The production and processing of crude petroleum and natural gas are the dominant economic sectors of the Middle East, providing more than 80 % of the region's foreign exchange. In 1992, the 15 countries that constituted the region accounted for 29.5 % of world crude petroleum output, 20 % of world natural gas plant liquid production, and 5 % of world dry natural gas production. Only Cyprus and Lebanon were not crude petroleum producers. A fairly wide range of non fuel minerals is also produced in the region. The most significant are boron minerals, bromine, chromite, gypsum, phosphate rock, potash, strontium, and sulfur. However, the variety of minerals produced, output levels, and the size of the overall non fuel mineral economy of the region is dominated by Iran and Turkey. Turkey, with a diverse mineral production and strategically situated between Europe and the Middle East, was first in world production of run-of-mine boron minerals, second in strontium behind Mexico, and fourth in pumice. It was also a significant world producer of chromite, magnesi'lm compounds, mercury, and sodium sulfate. Turkey was also the Middle East's largest cement and steel producer. Iran continued to expand output of most mineral commodities following the war with Iraq from 1980 to 1988. It was a significant world producer of gypsum and strontium and on its way to becoming a major iron and steel producer in the region. Despite a very small domestic mineral industry, Israel was second in world production of bromine and a significant producer of phosphate rock and potash. In terms of processed minerals, Israel was a major world diamond cutting center and exporter of cut diamond. Jordan ranked sixth in world production of phosphate rock. Saudi Arabia was eighth in world production of sulfur.